2018
DOI: 10.1111/cas.13819
|View full text |Cite
|
Sign up to set email alerts
|

Efficacy of liquid‐based genetic diagnosis of endometrial cancer

Abstract: Although liquid‐based cytology (LBC) has increased the sensitivity of cytological diagnosis of endometrial cancer (EC) compared with conventional smear cytology, the sensitivity of LBC for the detection of EC is between 70% and 96% and remains unsatisfactory. In the present study, we compared the efficacy of LBC with liquid‐based genetic diagnosis (LBGDx) by amplicon sequencing of five genes including PTEN,PIK3CA,CTNNB1,KRAS, and TP53 in 48 LBC subjects who underwent endometrial screening. Consequently, LBC cl… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
4
1

Citation Types

3
5
0

Year Published

2020
2020
2023
2023

Publication Types

Select...
4
2
2

Relationship

0
8

Authors

Journals

citations
Cited by 9 publications
(8 citation statements)
references
References 22 publications
3
5
0
Order By: Relevance
“…Analysis with our custom-built panel identified mutations in PTEN (79%), CTNNB1 (54%), PIK3R1 (42%), PIK3CA (58%), ARID1A (67%), and TP53 (21%) in the FFPE specimens, and these variant frequencies agree with previous reports [ 40 – 42 ]. In 9 of 10 endometrial LBC samples, genetic analysis was successfully completed with PTEN (56%), CTNNB1 (44%), PIK3R1 (33%), PIK3CA (56%), ARID1A (56%), and TP53 (33%) mutation frequencies comparable to those previously reported based on amplicon sequencing for 5 genes ( PETN, PIK3CA, CTNNB1, KRAS, and TP53 ), in which at least one pathogenic variant was identified in 17 of 20 cases (85%) [ 43 ]. Of note, a few differences in genomic profiles among different specimens from the same patients were observed.…”
Section: Discussionsupporting
confidence: 62%
“…Analysis with our custom-built panel identified mutations in PTEN (79%), CTNNB1 (54%), PIK3R1 (42%), PIK3CA (58%), ARID1A (67%), and TP53 (21%) in the FFPE specimens, and these variant frequencies agree with previous reports [ 40 – 42 ]. In 9 of 10 endometrial LBC samples, genetic analysis was successfully completed with PTEN (56%), CTNNB1 (44%), PIK3R1 (33%), PIK3CA (56%), ARID1A (56%), and TP53 (33%) mutation frequencies comparable to those previously reported based on amplicon sequencing for 5 genes ( PETN, PIK3CA, CTNNB1, KRAS, and TP53 ), in which at least one pathogenic variant was identified in 17 of 20 cases (85%) [ 43 ]. Of note, a few differences in genomic profiles among different specimens from the same patients were observed.…”
Section: Discussionsupporting
confidence: 62%
“…Analysis with our custom-built panel identified mutations in PTEN (79%), CTNNB1 (54%), PIK3R1 (42%), PIK3CA (58%), ARID1A (67%), and TP53 (21%) in the FFPE specimens, and these variant frequencies are in good agreement with previous reports [35][36][37]. Genetic analysis using endometrial LBC samples showed a total sensitivity of 90% (9/10) with comparable mutation frequencies in PTEN (56%), CTNNB1 (44%), PIK3R1 (33%), PIK3CA (56%), ARID1A (56%), and TP53 (33%) to those previously reported based on amplicon sequencing for 5 genes (PETN, PIK3CA, CTNNB1, KRAS, and TP53) in which at least one pathogenic variant was identified in 17 of 20 cases (85%) [38]. There observed few differences in genomic profile among different specimens from the same patients.…”
Section: Discussionsupporting
confidence: 60%
“…Analysis with our custom-built panel identi ed mutations in PTEN (79%), CTNNB1 (54%), PIK3R1 (42%), PIK3CA (58%), ARID1A (67%), and TP53 (21%) in the FFPE specimens, and these variant frequencies agree with previous reports [40][41][42]. In 9 of 10 endometrial LBC samples, genetic analysis was successfully completed with PTEN (56%), CTNNB1 (44%), PIK3R1 (33%), PIK3CA (56%), ARID1A (56%), and TP53 (33%) mutation frequencies comparable to those previously reported based on amplicon sequencing for 5 genes (PETN, PIK3CA, CTNNB1, KRAS, and TP53), in which at least one pathogenic variant was identi ed in 17 of 20 cases (85%) [43]. Of note, a few differences in genomic pro les among different specimens from the same patients were observed.…”
Section: Discussionsupporting
confidence: 58%